Polymerisation of ethylene : in slurry loop reactors - Allemeersch, Paul (Walter de Gruyter GmbH & Co., KG, 2015)
This book is based on full scale experience, and allows to understand the functioning of the slurry loop reactor, and to operate it. All necessary aspects of the reactor are treated, and then combined in a simple off-line model, valid for all commercial types of catalysts. A detailed method to scale-up products from the laboratory directly to the full scale loop reactor is given.